Association of Anthropometric Indices With Metabolic Phenotypes of Obesity in Children and Adolescents: The CASPIAN-V Study - Payab, Moloud; Qorbani, Mostafa; Shahbal, Nazila; Motlagh, Mohammad Esmaeil; Hasani-Ranjbar, Shirin; Zahedi, Hoda; Shafiee, Gita; Ziaodini, Hasan; Pourmirzaiee, Mohammad Ali; Heshmat, Ramin; Kelishadi, Roya (Frontiers in Endocrinology, 2019)
Background Obesity, particularly in the upper part of body, is a major health problem. Neck circumference (NC) and wrist circumference (WrC) is a relatively new method of differentiating between normal and abnormal fat distributions. This study aimed to evaluate the association of NC, hip circumference (HC), and WrC with different phenotypes of obesity and their metabolic status. Methods In this multi-centric cross-sectional study, 4200 students aged 7–18 years were selected using multistage cluster random sampling method from 30 provinces of Iran in 2014. Metabolic syndrome (MetS) was defined based on the ATP III criteria modified for the pediatric age group. The subjects were classified into four groups according to their weight and metabolic status: metabolically healthy obese (MHO), metabolically non-healthy non-obese (MNHNO), metabolically non-healthy obese (MNHO), and metabolically healthy non-obese (MHNO). Results A significant but different association was documented between NC, HC, and WrC and obesity phenotypes in the entire population. Also, a significant but different association was found between NC, HC, and WrC and metabolic phenotypes in the entire population. In the multinomial logistic regression, the association of the different obesity phenotypes with the study anthropometric indices increased significantly by increasing NC, WrC, and HC. Also per one unit increment in NC, HC, and Wrc the odds of MHO, MNHNO, MNHO increased compared to the MHNO phenotype. Conclusion In children and adolescents, HC, NC and WrC are significantly associated with obesity phenotypes and their metabolic status, and are suggested to be innovativ, low-cost, and alternative tools for assessing them in different age and sex pediatric age groups.